Droits fonciers coutumiers et autonomie regionale a Kalimantan a Kalimantan-Est (Indonesie): entre enjeux de pouvoir et contrôle de l’accès aux ressources. - Levang, P.; Buyse, N. (2007)
According to the Indonesian constitution of 1945, customary rights are only recognized if not in contradiction with the superior interests of the Nation. The contradiction is most blatant in matters of forest management. Under the Dutch colonial rule as well as under the auspices of the young independent republic, the rights of forest peoples over their resources were always denied. Forest management is entrusted to the Ministry of Forestry who controls more than 70% of the total surface of the archipelago. The central power only recognizes tenure rights to local populations on cultivated land: rice fields and plantations. Primary forest and forest re-growth are considered property of the State, in clear opposition to the customary laws for which the right of axe is inalienable. Under the sinewy dictatorship of General Suharto, the indigenous peoples were forced to silently witness the plunder of their forest resources without any compensation. The situation changed entirely with the fall of Suharto in 1998 and the implementation of the regional autonomy from 1999 onwards. For long despised and ignored by the central power, the indigenous populations, sustained in it by indigenist NGOs and the new political parties allowed, asked for the respect of their customary laws and the recognition of their tenure rights. In East-Kalimantan, the revival of adat proved to be more complicated than anticipated. On the one hand, the indigenous ethnic groups always showed a strong spatial mobility, on the other hand, the province has welcomed migrants in numbers largely superior to the natives. History and archaeology became the local populations’ new hobbies. The recourse to history and the research of archaeological vestiges have only one goal: to prove the antecedence of the occupation of the territory, and thus to justify the demands of royalties for the exploitation of natural resources.